The Influence of Democratic Leadership Style and Communication on Employee Productivity PT. Asia Surya Perkasa Pangkal Pinang - Fernando Josse; Siti Komariah Hildayanti; Mohammad Kurniawan DP (ProBisnis : Jurnal Manajemen, 2023)
The purpose of this study was to analyze the description of the role of democratic leadership style and communication on work productivity at PT Asia Surya Perkasa Pangkal Pinang. The population in this study were 66 employees who were total saturated sampling. Research data collection was carried out by observation and distributing questionnaires. The analysis technique used is multiple linear regression analysis, validity test and classical assumption test. Based on the results of analysis and hypothesis testing, democratic leadership style has a positive and significant effect on the work productivity of employees of PT Asia Surya Perkasa Pangkal Pinang, communication has a positive and significant effect on the work productivity of employees of PT Asia Surya Perkasa Pangkal Pinang. With the results (1) there is a positive and significant influence in the t test results where the tcount> ttable value or that the calculated tvalue for the democratic leadership style is 8.346> from ttable 1.998 with a significance level of 0.050 <0.05, and communication has a calculated t value = 12.303 > from ttable 1.998 with a significance level of 0.000 <0.05, (2) The Fcount value is 75.579 with a Ftable value of 3.14 so that the Fcount value is 75.579 with a Ftable value of 3.14. is 3.14 so that the value of Fcount> Ftable or 75.579> 3.14 and a significance level of 0.000 <0.05, (3) The coefficient value of R Square (R2) is 0.706 or 70.6 percent so that the magnitude of the influence of communication variables and democratic leadership style on employee work productivity is 70.6 %